2008
DOI: 10.1674/0003-0031(2008)160[171:mcowmp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Captures of White-Footed Mice (Peromyscus Leucopus): Evidence for Social Structure?

Abstract: Multiple captures (34 double, 6 triple) in standard Sherman live traps accounted for 6.3% of 1355 captures of Peromyscus leucopus (white-footed mice) in forested habitat in southern Illinois, from Oct. 2004 through Oct. 2005. There was a significant positive relationship between both the number and the proportion of multiple captures and estimated monthly population size. Multiple captures were all intraspecific and occurred significantly more often from Nov. through Mar. when animals were not reproductively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(37 reference statements)
2
0
0
Order By: Relevance
“…We addressed how males and females interacted and found the mixing patterns to be constant among our sites with no response to treatment. This finding is similar to a network analysis of male-female mixing in yellow-necked mice, Apodemus flavicollis, in northern Italy, where male-female assortativity was consistently invariant (Perkins et al 2008) and a study of multiple live-captures that reported a random mixing of sex from trapping data of P. leucopus in southern Illinois, USA (Feldhamer et al 2008). While other observational and network approaches have reported contacts assorted within sex more often than between sexes in white-tailed deer (Odocoilus virgianus, observations: Nixon et al 1991) and bottle-nosed dolphins (Tursiops spp., networks: Lusseau & Newman 2004), random mixing by sex may be more characteristic than previously assumed in some rodent species.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We addressed how males and females interacted and found the mixing patterns to be constant among our sites with no response to treatment. This finding is similar to a network analysis of male-female mixing in yellow-necked mice, Apodemus flavicollis, in northern Italy, where male-female assortativity was consistently invariant (Perkins et al 2008) and a study of multiple live-captures that reported a random mixing of sex from trapping data of P. leucopus in southern Illinois, USA (Feldhamer et al 2008). While other observational and network approaches have reported contacts assorted within sex more often than between sexes in white-tailed deer (Odocoilus virgianus, observations: Nixon et al 1991) and bottle-nosed dolphins (Tursiops spp., networks: Lusseau & Newman 2004), random mixing by sex may be more characteristic than previously assumed in some rodent species.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is similar to a network analysis of male‐female mixing in yellow‐necked mice, Apodemus flavicollis, in northern Italy, where male‐female assortativity was consistently invariant (Perkins et al. 2008) and a study of multiple live‐captures that reported a random mixing of sex from trapping data of P. leucopus in southern Illinois, USA (Feldhamer et al. 2008).…”
Section: Discussionsupporting
confidence: 82%